2019
DOI: 10.4310/mrl.2019.v26.n1.a12
|View full text |Cite
|
Sign up to set email alerts
|

Randomized final-data problem for systems of nonlinear Schrödinger equations and the Gross–Pitaevskii equation

Abstract: We consider the final-data problem for systems of nonlinear Schrödinger equations (NLS) with L 2 subcritical nonlinearity. An asymptotically free solution is uniquely obtained for almost every randomized asymptotic profile in L 2 (R d ), extending the result of J. Murphy [29] to powers equal to or lower than the Strauss exponent. In particular, systems with quadratic nonlinearity can be treated in three space dimensions, and by the same argument, the Gross-Pitaevskii equation in the energy space. The extension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…We are now ready to provide the improvement in space-time integrability of the linear flow e it∆ f ω with data randomized in frequency space, the angular variable and in physical space which originates in the unit-scale decomposition in physical space. We obtain the same set of estimates as for the pure physical-space randomization, see [36,28]. Hence, the additional randomization in frequency space and the angular variable does not impair the improvements of the physical-space randomization.…”
Section: Probabilistic Estimatesmentioning
confidence: 74%
See 3 more Smart Citations
“…We are now ready to provide the improvement in space-time integrability of the linear flow e it∆ f ω with data randomized in frequency space, the angular variable and in physical space which originates in the unit-scale decomposition in physical space. We obtain the same set of estimates as for the pure physical-space randomization, see [36,28]. Hence, the additional randomization in frequency space and the angular variable does not impair the improvements of the physical-space randomization.…”
Section: Probabilistic Estimatesmentioning
confidence: 74%
“…Roughly speaking, this randomization allows to employ the dispersive estimate for solutions of the linear Schrödinger equation although the data only belongs to L 2 . These techniques were further refined in [28].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Roughly speaking, the physical-space randomization gives access to the dispersive estimate for linear solutions of the Schrödinger equation although the data only belongs to L 2 . In [38] the authors observed that this dispersive decay can be used to study the final-state problem in time-weighted spaces, improving on the results in [37].…”
Section: Introduction and Main Resultsmentioning
confidence: 82%